Tinjauan Hukum Dosen Pegawai Negeri Sipil Merangkap Profesi sebagai Advokat Pasca Putusan Mahkamah Konstitusi Nomor 150/PUU-XXII/2024 - Firda Nisa Syafithri; Moch. Dinul Faqih (Lembaga Yasin AlSys, 2025)
The Constitutional Court Decision Number 150/PUU-XXII/2024 has sparked considerable debate regarding the independence of the legal profession and the integrity of Indonesia’s legal system, particularly in the context of dual roles held by civil servant (PNS) lecturers who also serve as advocates. The core issue lies in the potential conflict of interest between the civil servant's loyalty to the state and the professional demand for advocate independence. This study aims to examine the implications of the decision for the advancement of academia and the integrity of the legal profession, and to assess whether it supports the implementation of the Tri Dharma Perguruan Tinggi or instead sets a precedent that threatens advocate independence. The research employs a normative-empirical juridical approach, analyzing Law Number 18 of 2003 on Advocates, the Constitutional Court's ruling, and empirical data gathered through observation and interviews with legal academics and practitioners. The findings indicate that the dual role of PNS lecturers as advocates, if managed ethically and professionally, can yield positive contributions to both the legal system and higher education. First-hand legal practice enhances the contextual and practical dimensions of legal education, thereby strengthening the synergy between theory and practice. Nevertheless, the potential for conflicts of interest and the risk of compromised professional independence must be mitigated through clear regulatory frameworks and robust oversight mechanisms. This study offers a conceptual contribution to policy formulation that harmonizes the Law on State Civil Apparatus and the Advocate Law, while also enriching academic discourse on the redefinition of lecturers’ roles as agents of change within Indonesia’s legal system.